2018
DOI: 10.1016/j.wneu.2018.07.188
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal Enhancement Is Associated with Transient Neurologic Deficits after Flow Diversion of Intracranial Aneurysms

Abstract: This study challenges conventional dogma that TNDs are ischemic in etiology and suggests blood-brain barrier impairment may be a potential alternative mechanism. These findings are applicable to stroke and other reversible neurologic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Most studies were performed in cases with ischemic stroke, transient ischemic attack (TIA), and/or intracerebral hemorrhage (ICH) (n = 20) ( Villringer, 2017 , Ostwaldt, 2015 , Ostwaldt, 2014 , Warach and Latour, 2004 , Latour et al, 2004 , Choi, 2017 , Dechambre, 2000 , Forster et al, 2016 , Gupta, 2017 , Henning et al, 2008 , Hjort, 2008 , Kim, 2005 , Luby, 2019 , Nadareishvili, 2018 , Lee, 2015 , Lee, 2016 , Lee, 2018 , Rozanski, 2010 , Kidwell et al, 2011 , Jolink, et al, 2019 , Barr, 2010 ). Six studies described patients who underwent cardiovascular or intracranial vascular surgery ( Cho, 2014 , Ogami et al, 2011 , Wilkinson, 2000 , Li, 2018 , Suthiphosuwan et al, 2018 , Merino, 2013 ), nine studies patients with multiple sclerosis (MS) (one of these included stroke cases as a positive control ( Eisele, 2015 ) ( Eisele, 2015 , Absinta, 2015 , Bergsland, 2019 , Harrison, 2017 , Jonas et al, 2018 , Zivadinov, 2017 , Zivadinov, 2018 , Zurawski, 2020 , Ighani, 2020 ), four studies patients with meningitis ( Ahmad et al, 2015 , Alonso, 2015 , Fukuoka, 2010 , Splendiani, 2005 ), two studies reported on memory clinic patients and normal aging ( Freeze, 2017 , Freeze et al, 2019 ), one study on Susac syndrome and MS ( Coulette, 2019 ), one study on familial amyloid polyneuropathy ( Hirai, 2005 ), and one study included a mix of diseases, which were presented as follows: inflammatory and immune-mediated neurologic diseases (neuromyelitis optica spectrum disorder, immune-mediated encephalitis, immune-mediated cerebellar ataxia, systemic inflammatory diseases with white matter MRI abnormalities not suggestive for MS and Susac syndrome), noninflammatory neurologic diseases (small vessel disease, migraine, neurodegenerative diseases, compressive myelopathy), human T-lymphotropic virus (HTLV) infection, and human immun...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies were performed in cases with ischemic stroke, transient ischemic attack (TIA), and/or intracerebral hemorrhage (ICH) (n = 20) ( Villringer, 2017 , Ostwaldt, 2015 , Ostwaldt, 2014 , Warach and Latour, 2004 , Latour et al, 2004 , Choi, 2017 , Dechambre, 2000 , Forster et al, 2016 , Gupta, 2017 , Henning et al, 2008 , Hjort, 2008 , Kim, 2005 , Luby, 2019 , Nadareishvili, 2018 , Lee, 2015 , Lee, 2016 , Lee, 2018 , Rozanski, 2010 , Kidwell et al, 2011 , Jolink, et al, 2019 , Barr, 2010 ). Six studies described patients who underwent cardiovascular or intracranial vascular surgery ( Cho, 2014 , Ogami et al, 2011 , Wilkinson, 2000 , Li, 2018 , Suthiphosuwan et al, 2018 , Merino, 2013 ), nine studies patients with multiple sclerosis (MS) (one of these included stroke cases as a positive control ( Eisele, 2015 ) ( Eisele, 2015 , Absinta, 2015 , Bergsland, 2019 , Harrison, 2017 , Jonas et al, 2018 , Zivadinov, 2017 , Zivadinov, 2018 , Zurawski, 2020 , Ighani, 2020 ), four studies patients with meningitis ( Ahmad et al, 2015 , Alonso, 2015 , Fukuoka, 2010 , Splendiani, 2005 ), two studies reported on memory clinic patients and normal aging ( Freeze, 2017 , Freeze et al, 2019 ), one study on Susac syndrome and MS ( Coulette, 2019 ), one study on familial amyloid polyneuropathy ( Hirai, 2005 ), and one study included a mix of diseases, which were presented as follows: inflammatory and immune-mediated neurologic diseases (neuromyelitis optica spectrum disorder, immune-mediated encephalitis, immune-mediated cerebellar ataxia, systemic inflammatory diseases with white matter MRI abnormalities not suggestive for MS and Susac syndrome), noninflammatory neurologic diseases (small vessel disease, migraine, neurodegenerative diseases, compressive myelopathy), human T-lymphotropic virus (HTLV) infection, and human immun...…”
Section: Resultsmentioning
confidence: 99%
“…When these studies were combined, the pooled prevalence estimate was 40% (95% CI 30–51). Two studies examined a total of 99 cases with a pooled mean age of 58 years who underwent unruptured aneurysm treatment and reported prevalence numbers of 52% ( Suthiphosuwan et al, 2018 )and 83% ( Li, 2018 ), with a combined prevalence estimate of 64% (95% CI 54–73). In addition, one study in 19 cases (mean age 67 years) who underwent cardiac surgery reported a prevalence of 47% ( Merino, 2013 )( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found a significant relationship between pcFLAIR enhancement and development of post-procedure neurological deficits in a small series of patients who underwent flow diversion therapy [9]. The current study focuses on the relationship between various clinical variables and the presence and extent of LME on postoperative imaging following neuroangiographic procedures.…”
Section: Flow Diversion Therapy Is Associated With Lme On Pcflair Imagingmentioning
confidence: 94%
“…LME on pcFLAIR has been increasingly identified and targeted as an important imaging biomarker following endovascular surgery due to its prognostic value after stroke intervention, but the incidence and pathophysiology of LME remain unknown [8]. We previously found a significant relationship between pcFLAIR enhancement and development of post-procedure neurological deficits in a small series of patients who underwent flow diversion therapy [9]. The aim of this study is to investigate the relationship of various clinical variables on the development of pcFLAIR abnormalities in patients undergoing elective flow diversion of intracranial aneurysms.…”
Section: Introductionmentioning
confidence: 99%